Psychological Capital and Career Commitment Among Chinese Urban Preschool Teachers: The Mediating and Moderating Effects of Subjective Well-being - Gan, Yongtao; Cheng, Li (Frontiers in Psychology, 2021)
This study explored the effects of psychological capital on career commitment among preschool teachers in China, with a particular focus on the mediating effects of subjective well-being. A total of 759 teachers were subjected to the Psychological Capital Questionnaire and Career Commitment Scale. The data were analyzed and used for structural modeling with Mplus Version 7.4. Results indicated that psychological capital positively influenced career commitment, with subjective well-being significantly mediating and moderating this causal association. Thus, the influence of PsyCap on career commitment is improved through enhanced subjective well-being. These findings highlight avenues for improving both PsyCap and career commitment in the Chinese context among urban preschool teachers.